ANALISIS TINGKAT KEPUASAN TAMU YANG MENGINAP ATAS KUALITAS PELAYANAN “PATI HOTEL” DI KOTA PATI - Andra Barata Putra; Nawazirul Lubis; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2013)
Hotel is a service company that is known to the services offered. No matter how good the physical condition of a building that hotel if it is not supported by the maximum service to customers who have stayed, consumers still are not satisfied. Based on this formulation of the problem in the study was a decrease in the number of guests staying in Pati Hotel from 2009 s / d 2012. This study aims to determine the level of compatibility between the expectations of guests who stay and the performance of services provided and to determine the level of guest satisfaction Pati Hotel on the quality of services provided by Pati Hotel. This type of research is descriptive by using primary data. The data was collected by guiding question for obtaining data from the company, while to obtain data from 100 respondents using a questionnaire. The sampling technique used was purposive sampling and accidental sampling. Furthermore, the data obtained in the field is processed in the form of tabulations that are then analyzed. Data analysis method used is descriptive qualitative. The results of the calculation, the fit between expectations and performance are Pati Hotel overall implementation of 85.81% can be considered quite as expected guests. Although the dimensions of reliability as hotel employees provide friendly services to the guest judged not fit 83.74%, are easy to book a hotel room does not match rated 83.95% and ensuring security of guest luggage in the hotel room was incompatible assessed 81.95 %. The results of calculation of the level of satisfaction of hotel guests, the performance of Pati Hotel by 4.13% to 4.81% guest expectations. General conclusion, guests feel quite satisfied with the performance of services in Pati Hotel. Advice can be given in this study include the management Pati Hotel needs to create variation in service serves breakfast, need installation of WIFI networks in the area of Pati Hotel, attach rates existing facilities in Pati Hotel in locations easily seen by guests.